Comparative Analysis of Actual Cost and INA CBG Rate in Diabetic Gangrene Inpatients - Diajeng Putri Kinanti; Umi Athiyah; Yunita Nita; Muhammad Noor Diansyah (Universitas Airlangga, 2021)
Background: Diabetic gangrene is a complication of diabetes mellitus that imposes a substantial financial burden on patients and their families as well as the health care system. Objective: To determine the total cost of disease, and the difference between real cost and INA CBG rate for diabetic gangrene inpatients from January - December 2017 at Universitas Airlangga Hospital, Surabaya Methods: The study was conducted retrospectively by using a total sampling method. The perspective used was the hospital perspective. This study's direct medical costs were laboratory, drug and consumable medical device costs, medical equipment rental, radiology examination, red cross, oxygen, service, and room costs. Data analysis was performed using an independent samples t-test. Results: The results showed that 148 patients met the inclusion criteria. The total real cost of diabetic gangrene inpatients at Universitas Airlangga Hospital in 2017 was IDR 1,339,949,381, and the total INA CBG rate for inpatients with diabetic gangrene was IDR 1,365,047,500. The difference was (p = 0.000) between real cost and INA CBG rate. Conclusion: There is a difference between the actual cost and the INA CBG rate for diabetic gangrene inpatients.